Composite ceramic glaze and preparation method and application method thereof
Through the composite of composite ceramic glaze and nanomaterial dispersion technology, combined with microwave sintering technology, the problem of the phosphor not resistant to heat at high temperatures of ceramic glaze is solved, and the good fluorescence and long afterglow effect of curbs are achieved, which improves the Safety and product life.
Patent Information
- Application Number
- CN202411449734.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-17
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2044-10-17
AI Technical Summary
The existing ceramic glaze is not heat-resistant during high-temperature sintering, resulting in poor fluorescence effect after automobile light absorption, making it difficult to serve as a warning effect, and the reflector strip’s life is short and difficult to clean, which poses safety hazards.
By combining composite ceramic glaze, the sintering temperature is reduced, the phosphor is doped and the film layer is coated on its surface, which improves dispersion and stability. Combined with the dispersion technology of nanomaterials and microwave sintering technology, good fluorescence performance is prepared to be prepared by combining the dispersion technology of nanomaterials and microwave sintering technology. and glaze with long afterglow effect.
It realizes the stability and performance of phosphor under low-temperature sintering conditions, improves the fluorescence effect and all-weather visibility of curbs, extends product life, and reduces the impact of high temperature on fluorescent materials.
Smart Images

Figure CN118978339B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of ceramic glaze production, in particular to a composite ceramic glaze and a preparation method and an application method thereof. Background Art
[0002] Ceramic glaze is a decorative and protective material used on the surface of ceramic products. It is usually composed of a variety of mineral raw materials and chemical substances, and is made through fine processing and blending. Ceramic glaze melts at high temperature and covers the surface of the ceramic body to form a smooth, hard and beautiful coating. It can improve the appearance of ceramic products and give them rich colors and luster. It can also improve the wear resistance, corrosion resistance and waterproofness of ceramics and extend their service life. As an important facility on the edge of the road, curbstones play a key role in transportation and urban construction. However, ordinary curbstones are indeed difficult to distinguish when visibility is poor at night, which poses a great safety hazard to pedestrians and vehicles. Especially in the absence of street lights or dim light, collision accidents are very likely to occur. In reality, reflective strips are often pasted on curbstones to increase their reflective properties, but reflective strips have a short life (need to be replaced in 2-3 months), are difficult to clean when replaced, and have no warning effect on pedestrians when the light is weak at night.
[0003] There is a certain difference between the wavelength of car lights and sunlight. Sunlight is a composite light that contains various wavelengths from ultraviolet to infrared. Car lights are mainly composed of visible light of a specific wavelength, and its wavelength range is approximately between 300-700 nanometers; in comparison, the wavelength range of car lights is relatively narrow, and the intensity is also different from sunlight. Phosphor is a substance that can emit fluorescence when excited by light of a specific wavelength. When phosphor is exposed to light, it absorbs light of a specific wavelength and converts it into fluorescence of a different wavelength and emits it.
[0004] Chinese patent application CN108658463A, published on December 25, 2020, discloses a fluorescent glaze, a fluorescent ceramic product made of the same, and a method for manufacturing the same. The fluorescent glaze is composed of fluorescent powder, borax, and an appropriate amount of glass powder and zinc oxide, and the glass powder is obtained by grinding discarded colorless ordinary glass. It is just a simple combination of fluorescent powder and glaze, which is not suitable for curbstone glaze.
[0005] In summary, the existing technology can add some fluorescent powder into the glaze to achieve the fluorescent effect, but there are problems such as poor fluorescent effect and the fluorescent powder is not resistant to high-temperature sintering, which makes it difficult to achieve the purpose of generating fluorescence (reflection) after absorbing car lights to play a warning role. Summary of the invention
[0006] In view of the above deficiencies in the prior art, the purpose of the present invention is to provide a composite ceramic glaze. By compounding the raw materials in the glaze, the sintering temperature is greatly reduced, thereby providing conditions for the addition of phosphors. By doping and compounding the phosphors and coating the surface with a film layer, not only the dispersibility but also the stability at high temperatures are improved. In the later sintering process, the internal structure of the phosphors changes little and can exhibit better fluorescence properties.
[0007] Another object of the present invention is to provide a method for preparing a composite ceramic glaze, which greatly improves the mixing uniformity and the dispersibility of the nanomaterials by mixing them separately and then merging them, so that the glaze has suitable viscosity and fluidity, which is convenient for glazing operation.
[0008] The third object of the present invention is to provide an application method of a composite ceramic glaze for the preparation of curbstones. The preparation process has a low sintering temperature and a short sintering time. While ensuring the strength of the curbstone, it minimizes the impact of high temperature on fluorescent materials and greatly improves product performance.
[0009] The present invention is achieved by adopting the following technical solutions:
[0010] The composite ceramic glaze comprises the following raw materials in parts by weight: quartz: 20-35 parts; kaolin: 15-25 parts; feldspar: 20-30 parts; talc: 4-10 parts; boric acid: 2-5 parts; limestone: 8-15 parts; nano silicon dioxide: 1-3 parts; nano aluminum oxide: 1-4 parts; silver-loaded zeolite: 1-3 parts; nano titanium dioxide: 1-4 parts; zinc oxide: 1-3 parts; silicon powder: 1-2 parts; magnesium oxide: 1-2 parts; zirconium oxide: 1-3 parts; cerium oxide: 0.5-1.5 parts; lanthanum oxide: 0.5-2 parts; lithium fluoride: 0.5-3 parts; luminescent phosphor: 0.5-3 parts; long afterglow phosphor: 0.5-2 parts.
[0011] The composite ceramic glaze further comprises sodium hexametaphosphate, bentonite and water, wherein the amount of bentonite added is 3.2-3.8% of the total mass of the glaze, and the amount of water added is 32-35% of the total mass of the glaze. The amount of water added here refers to the amount of water added as a solvent when all powders (raw materials) are prepared, and has nothing to do with the solvent used in the separate preparation process of the phosphor.
[0012] The silicon dioxide content in the quartz is 96-98%; the kaolinite content in the kaolin is 80-85%; the potassium feldspar content in the feldspar is 46-55%, the sodium feldspar content is 27-36%, and the calcium feldspar content is 12-18%; the hydrated magnesium silicate content in the talc is 92-94%; the montmorillonite content in the bentonite is 86-89%; and the silver content in the silver-loaded zeolite is 1.3-3.2%.
[0013] Potassium feldspar, sodium feldspar and calcium feldspar work together to improve the performance of glazes. Potassium feldspar melts at high temperatures and can reduce the melting temperature of glazes. The glass phase formed after melting can fill the pores in the glaze layer, making the glaze surface smoother and flatter, thereby improving the gloss of the glaze surface. Sodium feldspar can work synergistically with potassium feldspar to further adjust the melting temperature range of the glaze. This allows the glaze to maintain good fluidity at different temperature stages, which is conducive to the uniform coverage and densification of the glaze layer. The glass phase formed after the melting of sodium feldspar has a high transparency, which can make the glaze surface clearer and more transparent. Calcium feldspar can enhance the mechanical properties of the glaze and improve the wear resistance and impact resistance of ceramic products.
[0014] The method for preparing the luminescent fluorescent powder comprises the following steps:
[0015] (1) Weigh Y (NO3)3•6H2O, Eu (NO3)3•6H2O and Mg (NO3)2•6H2O, dissolve them in deionized water, and stir for 20-30 min to form solution A;
[0016] (2) Dissolve citric acid in deionized water, add NH4VO3, and stir for 30-40 minutes to form solution B;
[0017] (3) Add solution A dropwise to solution B while stirring continuously for 1.5-2 hours to form a sol; then place in an oven and dry at 65-75°C for 2-3 hours to form a gel; then heat to 135-155°C and dry for 5-8 hours to remove residual moisture and organic matter; grind the dried gel into powder;
[0018] (4) placing the powder obtained in step (3) in a muffle furnace protected by nitrogen, calcining at 735-750°C for 5-8 hours, and then starting to cool down, first at a rate of 3-5°C / min to 500°C, and then at a rate of 15-18°C / min to room temperature, to obtain a luminescent phosphor base material;
[0019] (5) taking the luminescent phosphor base obtained in step (4), dispersing it in anhydrous ethanol, and ultrasonically treating it for 30-45 minutes to form a suspension C;
[0020] (6) Take ethyl orthosilicate, add it to anhydrous ethanol, stir for 20-25 minutes, and form solution D;
[0021] (7) Add the suspension C dropwise into the solution D while stirring, add ammonia water, adjust the pH value to 9-10, and stir for 2.5-4 hours to promote the hydrolysis and polycondensation reaction of tetraethyl orthosilicate. After the reaction is completed, centrifuge the obtained product, collect the precipitate, wash the precipitate with anhydrous ethanol for 3-5 times, and then dry the precipitate at 75-80°C for 3-5 hours to obtain a luminescent phosphor;
[0022] The molar ratio of Y (NO3)3•6H2O, Eu (NO3)3•6H2O, Mg (NO3)2•6H2O and NH4VO3 is (0.9-0.95):0.05:(0.02-0.03):1; the amount of citric acid used is 1.2-2.2 times the amount of the total amount of metal ions; the mass ratio of the luminescent phosphor base material to tetraethyl orthosilicate is 1:(0.8-1.2); the total amount of anhydrous ethanol used is 7-9 times the volume of tetraethyl orthosilicate; in the step (1), the amount of deionized water used is Y (NO3)3•6H2O, Eu (NO3)3•6H2O and Mg The amount of deionized water used in step (2) is 2-3 times the mass of citric acid; and the addition rate in step (3) is 1-3 ml / min.
[0023] The method for preparing the long afterglow phosphor comprises the following steps:
[0024] ① Dissolve Ca (NO3)2•4H2O, Dy (NO3)3•6H2O and Zr (NO4)4•5H2O in deionized water and stir for 15-25 minutes to form solution E;
[0025] ② Dissolve Na2MoO4•2H2O in deionized water to form solution F;
[0026] ③ Add solution F drop by drop into solution E while stirring, adjust the pH value to 8.5-9 with NaOH solution, then transfer it to a hydrothermal reactor, place it in an oven, and react at 170-178°C for 18-24h. After the reaction, centrifuge the product, wash the precipitate with deionized water and anhydrous ethanol 3-5 times, and dry it at 65-75°C for 5-8h to obtain a long afterglow phosphor base material;
[0027] ④ Disperse the long afterglow phosphor base material into deionized water and perform ultrasonic treatment for 0.5-1h to form a suspension G;
[0028] ⑤ Dissolve Al (NO3)3•9H2O in deionized water to form solution H;
[0029] ⑥ Add solution H drop by drop into suspension G, start stirring at the same time, add ammonia water, adjust the pH value to 9.5-10, promote the hydrolysis and polycondensation reaction of Al (NO3)3•9H2O, after the reaction is completed, centrifuge the obtained product, wash the precipitate with deionized water and anhydrous ethanol 3-5 times, and dry it at 75-80℃ for 2.5-3h to obtain long afterglow phosphor;
[0030] The molar ratio of Ca (NO3)2•4H2O, Na2MoO4•2H2O, Dy (NO3)3•6H2O and Zr (NO4)4•5H2O is 1: (0.9-0.94): 0.05: (0.02-0.03); the mass ratio of the long afterglow phosphor base material to Al (NO3)3•9H2O is 1: (0.6-1); in the step ①, the amount of deionized water is Ca (NO3)2•4H2O, Dy (NO3)3•6H2O, Zr (NO4)4•5H2O, and Zr (NO4)4•5H2O. (NO3)3•6H2O and Zr(NO4)4•5H2O. In step ②, the amount of deionized water is 2-4 times the mass of Na2MoO4•2H2O. In step ③, the dripping speed is 1.5-4ml / min. In step ④, the amount of deionized water is 3-5 times the mass of the long afterglow phosphor base material. In step ⑤, the amount of deionized water is 3-5 times the mass of Al (NO3)3•9H2O. In step ⑥, when solution H is added dropwise into suspension G, the dripping speed is 1.5-3ml / min, and the dripping speed of ammonia water is 1-2 ml / min.
[0031] The particle size of the talc is 8-20 microns; the nano silicon dioxide is 12-28 nanometers and 62-74 nanometers silicon dioxide are compounded in a mass ratio of 2:1; the particle size of the nano aluminum oxide is 20-35 nanometers; the particle size of the nano titanium dioxide is 25-35 nanometers; the particle size of the silver-loaded zeolite is 3-7 microns; the particle size of the luminescent phosphor is 25-32 microns; and the particle size of the long afterglow phosphor is 25-35 microns.
[0032] The method for preparing the composite ceramic glaze comprises the following steps:
[0033] a. Screening of quartz, kaolin, feldspar and limestone, with particle size controlled at 50-80 microns;
[0034] b. Place nano-silicon dioxide, nano-alumina and nano-titanium dioxide in different mixers, add sodium hexametaphosphate respectively, mix for 1-1.5 hours, combine the materials in the three mixers, and continue mixing for 2-3 hours to obtain a nano-mixture; the mass ratio of sodium hexametaphosphate to nano-silicon dioxide is (4-5):100, the mass ratio of sodium hexametaphosphate to nano-alumina is (1-2):100, and the mass ratio of sodium hexametaphosphate to nano-titanium dioxide is (1-1.5):100;
[0035] c. The quartz, kaolin, and feldspar are placed in a mixing device for mixing, the mixing time is 30-70min, and then talc, boric acid, limestone, and silica powder are added, and stirring and mixing is continued for 45-60min, and then the nano-mixture prepared in step b is added, and stirring and mixing is continued for 2-3h, and then zinc oxide and magnesium oxide are added, and after stirring for 35-50min, silver-loaded zeolite, zirconium oxide, cerium oxide, and lanthanum oxide are added, and after stirring for 30-45min, lithium fluoride, luminescent phosphor and long afterglow phosphor are added, and the stirring speed is reduced, and stirring is continued for 2-3h to obtain a mixed powder;
[0036] d. The mixed powder obtained in step c is placed in a ball mill and milled for 12-18h, and the particle size after ball milling is not greater than 42 microns;
[0037] e. Stir the ball-milled mixed powder with water and bentonite for 3-4.5 hours to obtain a composite ceramic glaze.
[0038] The application method of the composite ceramic glaze is used for preparing kerbstones and can also be used for producing common ceramics, especially ceramics requiring fluorescent or reflective properties.
[0039] The method for preparing the kerbstone comprises the following steps:
[0040] (I) crushing and sieving clay, quartz, feldspar, talc, limestone, boric acid, titanium dioxide and magnesium oxide to obtain a mixture with a particle size of 15-25 microns as a mixed raw material;
[0041] (II) taking nano zirconium oxide and nano alumina, placing them in different containers, adding ethanol for ultrasonic dispersion, ultrasonication for 1-1.5 hours, and then drying at 50-65°C for 60-80 minutes to obtain nano powder zirconium oxide and nano powder alumina; dissolving carboxymethyl cellulose in water while stirring to form a carboxymethyl cellulose solution, the dissolution temperature of which is 45-55°C; taking silica sol, stirring for 1-1.5 hours;
[0042] (III) placing the mixed raw materials in step (I), the nano-powdered zirconium oxide and nano-powdered aluminum oxide in step (II), the carboxymethyl cellulose solution and the stirred silica sol in a ball mill in sequence, and performing ball milling mixing for a mixing time of 18-26 hours. After the mixing is completed, extrusion molding is performed to obtain a curbstone blank;
[0043] (IV) drying the curbstone body by microwave, the drying time is 3-6 hours, the drying temperature is 35-45°C, after the drying is completed, dipping the body in a composite ceramic glaze, the dipping time is 8-12 seconds, after the dipping is completed, drying at a temperature of 25-28°C and a relative humidity of 50% for 12-18 hours;
[0044] (V) Place the green body after glaze dipping and drying in a microwave sintering furnace, heat it to 465°C at a heating rate of 8°C / min, keep it at this temperature for 1 hour, then heat it to 975-990°C at a heating rate of 10°C / min, keep it at this temperature for 3-4 hours, then cool it to 300°C at a heating rate of 7°C / min, and then naturally cool it to room temperature to obtain a curbstone.
[0045] The curbstone blank comprises the following raw materials in parts by weight: clay: 35-42 parts; quartz: 18-21 parts; feldspar: 12-15 parts; talc: 2-3 parts; limestone: 1-3 parts; boric acid: 0.5-1 parts; titanium dioxide: 0.5-1 parts; magnesium oxide: 1-2 parts; nano zirconium oxide: 1-2 parts; nano aluminum oxide: 1-2 parts; carboxymethyl cellulose: 0.5-1 parts; silica sol: 2-4 parts; when the microwave sintering furnace is working, a mixed gas of hydrogen and nitrogen is introduced for protection. The volume ratio of hydrogen and nitrogen is (8-12): (80-92).
[0046] Quartz provides hardness and chemical stability, kaolin improves high temperature viscosity and chemical stability, and feldspar acts as a flux to reduce melting temperature and adjust viscosity and surface tension. The fluxing effect of feldspar can promote the melting of quartz and kaolin at a lower temperature to form a glass phase, thereby improving the overall performance of the glaze. Talc and boric acid work together to further reduce the sintering temperature of the glaze, reduce energy consumption, and improve the overall thermal stability, fluidity and wettability of the glaze, making the glaze smoother. Nano-silicon dioxide and nano-alumina work together to make the glaze have good stain resistance and resistance to wear and scratches. Silver-loaded zeolite and nano-titanium dioxide work together to enhance the antibacterial properties of the glaze, effectively inhibit the growth of bacteria and mold, and improve the finish of ceramic products. The combined action of zinc oxide and magnesium oxide can make the glaze more stable during the firing process. The synergistic action of zirconium oxide, cerium oxide and lanthanum oxide can comprehensively improve the performance of the glaze, so that ceramic products have better appearance quality and mechanical properties. The small size effect and high specific surface area of nanomaterials can fill the pores in the basic raw materials and enhance the mechanical properties and chemical stability of the glaze. The basic raw materials provide carriers and support for the antibacterial materials, while the antibacterial materials exert their antibacterial functions and jointly ensure the smoothness of ceramic products. Basic raw materials such as quartz, kaolin, and feldspar provide a stable matrix for phosphors, which emit fluorescence under the illumination of car lights.
[0047] The luminescent phosphor is made of rare earth doped yttrium vanadate phosphor (YVO4:Eu 3+ ) as the basis, and Mg was co-doped on it by sol-gel method. 2+ Ion, Mg 2+ Ions can enter the YVO4 crystal structure and replace part of the Y 3+ ions, enhance the stability of the crystal structure, improve thermal stability, and then coat a layer of SiO2 on its surface to effectively protect the phosphor particles and improve thermal stability; when the luminescent phosphor is excited by 350-500 nanometers of light in car lights, the response time is short, Eu 3+ The electrons of the ions will jump from the ground state to the excited state, and then emit strong fluorescence when returning to the ground state, which can strongly reflect the car lights, while for most other wavelengths of sunlight, it absorbs less and reflects relatively weakly. The SiO2 coating can reduce Eu 3+ The crystal field around the ions changes, thereby stabilizing the energy level structure of the luminescent center and improving the stability of luminescence. Long afterglow phosphors are made of rare earth-doped calcium molybdate phosphors (CaMoO4:Dy 3+ ) as the basis, and Zr was co-doped on it by hydrothermal method. 4+ Ion, Zr 4+ Ions can react with MoO4 2-The ions form a stable chemical bond, which improves the stability of the crystal structure and thus enhances thermal stability. A layer of Al2O3 is then coated on its surface to effectively protect the phosphor particles, improve thermal stability and oxidation resistance. During high-temperature sintering, alumina can form a solid solution with the calcium ions in calcium molybdate, reducing the diffusion and migration of ions at high temperatures and maintaining Dy 3+ The energy transfer process between the surrounding lattice ions and other doped ions; when the long afterglow phosphor is excited by 300-700 nanometers of light, it has a strong reflection effect (compared with the luminescent phosphor, the reflection time is slightly longer); it exhibits a strong long afterglow characteristic, and the afterglow time is long, and the reflection of other wavelengths in the sunlight is poor. During the high-temperature sintering process, the carbon powder can react with oxygen, consume the surrounding oxygen, and reduce the high-valent molybdenum ions that may be formed into low-valent molybdenum ions, keeping the crystal structure of calcium molybdate stable. Lithium fluoride can form stable yttrium fluoride with yttrium ions, reducing the volatilization and structural changes of yttrium ions.
[0048] Nano-silicon dioxide, nano-alumina and nano-titanium dioxide are placed in different mixers and mixed with sodium hexametaphosphate, and then combined together for further mixing. This treatment method can ensure that the nanomaterials are fully dispersed and avoid agglomeration. By mixing them separately and then combining them, sodium hexametaphosphate can be better adsorbed on the surface of nanoparticles, thereby improving the dispersibility of nanomaterials. For nano-silicon dioxide, the mass ratio of sodium hexametaphosphate to it is (4-5):100, which can effectively disperse the nano-silicon dioxide particles, make them evenly distributed in the glaze, and improve the density and anti-permeability of the glaze. The ball-milled mixed powder is stirred and mixed with water and bentonite for 3-4.5 hours. This time can ensure that the bentonite can fully exert its bonding effect, so that the glaze has suitable viscosity and fluidity, which is convenient for glazing operation. Nanomaterials have high specific surface area and surface activity, and can promote the sintering of glaze at a lower temperature. Lithium fluoride can form stable compounds with cations in phosphors, reducing the volatilization and structural changes of cations.
[0049] Nano zirconium oxide and nano alumina can fill the tiny pores between the body and the glaze to increase the bonding between the two. At the same time, the high specific surface area and activity of nano materials can promote the chemical reaction between the body and the glaze to form a stronger bond. The small size effect and high surface activity of nano materials can reduce the diffusion activation energy of the substance and promote the sintering reaction at a lower temperature. Carboxymethyl cellulose, as a binder, improves the strength and plasticity of the body. At the same time, it also helps the glaze to bond with the body during the glazing process and reduces the risk of glaze falling off. Silica sol can form a uniform siliceous film on the surface of the body to enhance the adhesion between the body and the glaze. At the same time, silica sol reacts with the components in the body and glaze at high temperature to further improve the bonding. Boric acid, as a flux, forms a liquid phase at a lower temperature, promotes the melting and sintering of other raw materials, and reduces the overall sintering temperature. Talc can improve the thermal stability of the body and also help to reduce the sintering temperature to a certain extent. The main raw materials such as clay, quartz, feldspar and other auxiliary raw materials cooperate with each other to provide the kerbstone with good strength, hardness, heat resistance and other properties. Microwave sintering is adopted, and the microwave energy is evenly distributed inside the material, making the overall temperature of the material uniform, reducing the material defects caused by uneven temperature.
[0050] Compared with the prior art, the present invention has the following beneficial effects:
[0051] (1) By compounding the raw materials in the glaze, the sintering temperature is greatly reduced, which provides conditions for the addition of phosphors. By doping and compounding the phosphors, a film layer is coated on their surface, which not only improves their dispersibility but also improves their stability at high temperatures. In the later sintering process, the internal structure of the phosphors changes little, and they can show good fluorescence performance and have self-cleaning properties.
[0052] (2) The composite ceramic glaze prepared by the present invention has obvious reflection of automobile light and weak reflection of sunlight, thus avoiding light pollution. At the same time, it also has a long afterglow effect, greatly improving its all-weather working ability.
[0053] (3) The kerbstone prepared by the present invention has a significant reaction to automobile lights of 300-700 nanometers while maintaining a relatively high intensity, producing a very good fluorescent effect (reflection) and at the same time, also having a good long afterglow effect.
[0054] (4) When preparing the composite ceramic glaze of the present invention, the mixing uniformity is greatly improved by mixing them separately and then merging them together, thereby improving the dispersibility of the nanomaterials, making the glaze have suitable viscosity and fluidity, and facilitating the glazing operation.
[0055] (5) When preparing the kerbstones, the sintering temperature is low and the sintering time is short. While ensuring the strength of the kerbstones, the influence of high temperature on the fluorescent material is minimized, thereby greatly improving the product performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0056] Figure 1 This is a temperature rise and fall curve diagram of the kerbstone prepared in Example 1 of the present invention;
[0057] Figure 2 This is the excitation spectrum of the material prepared in Example 1 of the present invention;
[0058] Figure 3 This is the afterglow curve of the material prepared in Example 1 of the present invention. The short dotted line at the bottom of the figure is the threshold value of the afterglow curve measurement, 0.12mcd / m 2 . DETAILED DESCRIPTION
[0059] In order to make the purpose and technical solution of the present invention more clear, the present invention is further described in detail.
[0060] Test method:
[0061] Wear resistance grade: GB / T3810.7-2016 "Test methods for ceramic tiles - Part 7: Determination of surface wear resistance of glazed tiles";
[0062] Mohs hardness: GB / T16534-2009 "Test method for room temperature hardness of fine ceramics";
[0063] Thermal expansion coefficient: GB / T16535-2008 Test method for thermal expansion coefficient of fine ceramic wires - ejector method;
[0064] Acid and alkali resistance: After soaking in an acid solution with a pH value of 2 for 72 hours, and then soaking in an alkali solution with a pH value of 12 for 72 hours, the mass loss rate of the curbstone was tested;
[0065] Thermal shock resistance: After 15 rapid heating and cooling cycles, from 80°C to -20°C, is there any crack defect in the curbstone?
[0066] Gloss: GB / T13891-2009 "Measurement method for specular gloss of building finishing materials";
[0067] Whiteness: QBT 1503-2011 "Determination method of whiteness of daily-use ceramics".
[0068] Fluorescence intensity: measured using a fluorescence spectrophotometer at an excitation wavelength of 450 nanometers. The fluorescence intensity value is expressed in relative fluorescence units.
[0069] Example 1
[0070] The composite ceramic glaze comprises the following raw materials in parts by weight: quartz: 30 parts; kaolin: 20 parts; feldspar: 25 parts; talc: 8 parts; boric acid: 3 parts; limestone: 12 parts; nano silicon dioxide: 2 parts; nano aluminum oxide: 3 parts; silver-loaded zeolite: 2 parts; nano titanium dioxide: 3 parts; zinc oxide: 2 parts; silicon powder: 2 parts; magnesium oxide: 2 parts; zirconium oxide: 2 parts; cerium oxide: 1 part; lanthanum oxide: 1 part; lithium fluoride: 2 parts; luminescent phosphor: 2 parts; long afterglow phosphor: 1 part; also comprises sodium hexametaphosphate, bentonite and water.
[0071] The silicon dioxide content in quartz is 97%; the kaolinite content in kaolin is 83%; the potassium feldspar content in feldspar is 50%, the sodium feldspar content is 36%, and the calcium feldspar content is 14%; the hydrated magnesium silicate content in talc is 93%; the montmorillonite content in bentonite is 88%; the silver content in silver-loaded zeolite is 2%.
[0072] The preparation method of the luminescent phosphor comprises the following steps:
[0073] (1) Weigh Y (NO3)3•6H2O, Eu (NO3)3•6H2O and Mg (NO3)2•6H2O, dissolve them in deionized water, and stir for 30 min to form solution A;
[0074] (2) Dissolve citric acid in deionized water, add NH4VO3, and stir for 40 min to form solution B;
[0075] (3) Add solution A dropwise to solution B while stirring continuously for 2 h to form a sol; then place in an oven and dry at 70 °C for 3 h to form a gel; then heat to 145 °C and dry for 6 h to remove residual moisture and organic matter; grind the dried gel into powder;
[0076] (4) placing the powder obtained in step (3) in a muffle furnace protected by nitrogen, calcining at 740° C. for 6 hours, and then starting to cool down, first at a rate of 4° C. / min to 500° C., and then at a rate of 16° C. / min to room temperature, to obtain a luminescent phosphor base material;
[0077] (5) taking the luminescent phosphor base material obtained in step (4), dispersing it in anhydrous ethanol, and ultrasonically treating it for 40 minutes to form a suspension C;
[0078] (6) Take ethyl orthosilicate, add it to anhydrous ethanol, stir for 23 minutes, and form solution D;
[0079] (7) Add the suspension C dropwise into the solution D while stirring, add ammonia water, adjust the pH value to 10, and stir for 3 h to promote the hydrolysis and polycondensation reaction of tetraethyl orthosilicate. After the reaction is completed, centrifuge the obtained product, collect the precipitate, wash the precipitate with anhydrous ethanol 4 times, and then dry the precipitate at 78 ° C for 4 h to obtain a luminescent phosphor;
[0080] The molar ratio of Y (NO3)3•6H2O, Eu (NO3)3•6H2O, Mg (NO3)2•6H2O and NH4VO3 is 0.92:0.05:0.03:1; the amount of citric acid used is twice the amount of the total amount of metal ions; the mass ratio of the luminescent phosphor base material to tetraethyl orthosilicate is 1:1; the total amount of anhydrous ethanol used is 8 times the volume of tetraethyl orthosilicate; in step (1), the amount of deionized water used is 3 times the sum of the masses of Y(NO3)3•6H2O, Eu (NO3)3•6H2O and Mg (NO3)2•6H2O; in step (2), the amount of deionized water used is 2.5 times the mass of citric acid; in step (3), the dripping speed is 1.5 ml / min.
[0081] The method for preparing a long afterglow phosphor comprises the following steps:
[0082] ① Dissolve Ca (NO3)2•4H2O, Dy (NO3)3•6H2O and Zr (NO4)4•5H2O in deionized water and stir for 20 min to form solution E;
[0083] ② Dissolve Na2MoO4•2H2O in deionized water to form solution F;
[0084] ③ Add solution F drop by drop into solution E while stirring, adjust the pH value to 8.8 with NaOH solution, then transfer it to a hydrothermal reactor, place it in an oven, and react at 178°C for 20 hours. After the reaction, centrifuge the product, wash the precipitate with deionized water and anhydrous ethanol 5 times, and dry it at 70°C for 8 hours to obtain a long afterglow phosphor base material;
[0085] ④ Disperse the long afterglow phosphor base material into deionized water and perform ultrasonic treatment for 1 hour to form a suspension G;
[0086] ⑤ Dissolve Al (NO3)3•9H2O in deionized water to form solution H;
[0087] ⑥ Add solution H drop by drop into suspension G, start stirring at the same time, add ammonia water, adjust the pH value to 9.7, promote the hydrolysis and polycondensation reaction of Al (NO3)3•9H2O, and after the reaction is completed, centrifuge the obtained product, wash the precipitate with deionized water and anhydrous ethanol three times, and dry it at 75℃ for 2.5h to obtain long afterglow phosphor;
[0088] The molar ratio of Ca (NO3)2•4H2O, Na2MoO4•2H2O, Dy (NO3)3•6H2O and Zr (NO4)4•5H2O is 1:0.92:0.05:0.02; the mass ratio of long afterglow phosphor base material to Al (NO3)3•9H2O is 1:0.8; in step ①, the amount of deionized water is 3 times the sum of the masses of Ca (NO3)2•4H2O, Dy (NO3)3•6H2O and Zr (NO4)4•5H2O; in step ②, the amount of deionized water is 3 times the mass of Na2MoO4•2H2O; in step ③, the dripping speed is 3ml / min; in step ④, the amount of deionized water is 4 times the mass of long afterglow phosphor base material; in step ⑤, the amount of deionized water is Al 4 times the mass of (NO3)3•9H2O; in step ⑥, when solution H is added dropwise to suspension G, the dropping speed is 2 ml / min, and the dropping speed of ammonia water is 2 ml / min.
[0089] The particle size of talc is 18 microns; nano silicon dioxide is compounded by 20 nanometers and 70 nanometers silicon dioxide in a mass ratio of 2:1; the particle size of nano alumina is 30 nanometers; the particle size of nano titanium dioxide is 30 nanometers; the particle size of silver-loaded zeolite is 5 microns; the particle size of luminescent phosphor is 30 microns; and the particle size of long afterglow phosphor is 30 microns.
[0090] The preparation method of the composite ceramic glaze comprises the following steps:
[0091] a. Screening of quartz, kaolin, feldspar and limestone, with particle size controlled at 65 microns;
[0092] b. Place nano-silicon dioxide, nano-alumina and nano-titanium dioxide in different mixers, add sodium hexametaphosphate respectively, mix for 1.5 hours, combine the materials in the three mixers, and continue mixing for 3 hours to obtain a nano-mixture; the mass ratio of sodium hexametaphosphate to nano-silicon dioxide is 5:100, the mass ratio of sodium hexametaphosphate to nano-alumina is 2:100, and the mass ratio of sodium hexametaphosphate to nano-titanium dioxide is 1.2:100;
[0093] c. The quartz, kaolin, and feldspar were placed in a mixing device for mixing, the mixing time was 55min, and then talc, boric acid, limestone, and silica powder were added, and stirring and mixing were continued for 50min, and then the nano-mixture prepared in step b was added, and stirring and mixing were continued for 3h, and then zinc oxide and magnesium oxide were added, and after stirring for 40min, silver-loaded zeolite, zirconium oxide, cerium oxide, and lanthanum oxide were added, and after stirring for 40min, lithium fluoride, luminescent phosphor and long afterglow phosphor were added, and the stirring speed was reduced and stirred for 3h to obtain a mixed powder;
[0094] d. The mixed powder obtained in step c was placed in a ball mill and milled for 16h, and the particle size after ball milling was 37 microns;
[0095] e. Stir the ball-milled mixed powder with water and bentonite for 4 hours to obtain a composite ceramic glaze.
[0096] The amount of water added is 35% of the total mass of the glaze; the amount of bentonite added is 3.6% of the total mass of the glaze.
[0097] The curbstone blank includes the following raw materials in parts by weight: clay: 40 parts; quartz: 20 parts; feldspar: 13 parts; talc: 3 parts; limestone: 2 parts; boric acid: 1 part; titanium dioxide: 1 part; magnesium oxide: 2 parts; nano zirconium oxide: 2 parts; nano aluminum oxide: 2 parts; carboxymethyl cellulose: 1 part; and silica sol: 3 parts.
[0098] The method for preparing the kerbstone comprises the following steps:
[0099] (I) crushing and sieving clay, quartz, feldspar, talc, limestone, boric acid, titanium dioxide and magnesium oxide to obtain a mixture with a particle size of 20 microns as a mixed raw material;
[0100] (II) Take nano zirconium oxide and nano alumina, place them in different containers, add ethanol for ultrasonic dispersion, ultrasonicate for 1.2 hours, and then dry at 60°C for 70 minutes to obtain nano powder zirconium oxide and nano powder alumina; dissolve carboxymethyl cellulose in water while stirring to form a carboxymethyl cellulose solution, the dissolution temperature is 50°C; take silica sol and stir for 1.2 hours;
[0101] (III) placing the mixed raw materials in step (I), the nano-powdered zirconium oxide and nano-powdered aluminum oxide in step (II), the carboxymethyl cellulose solution and the stirred silica sol in a ball mill in sequence, and performing ball milling mixing for 22 hours. After the mixing is completed, extrusion molding is performed to obtain a curbstone blank;
[0102] (IV) drying the curbstone body by microwave drying for 5 hours at a drying temperature of 41°C. After drying, dipping the body in a composite ceramic glaze for 10 seconds. After dipping, drying the body at a temperature of 28°C and a relative humidity of 50% for 16 hours.
[0103] (V) The green body after glaze dipping and drying is placed in a microwave sintering furnace, and a mixed gas of hydrogen and nitrogen (the volume ratio of hydrogen and nitrogen is 10:90) is introduced for protection. The temperature is increased to 465°C at a rate of 8°C / min, and kept at this temperature for 1 hour. Then, the temperature is increased to 985°C at a rate of 10°C / min, and kept at this temperature for 4 hours. Then, the temperature is decreased to 300°C at a rate of 7°C / min, and then naturally cooled to room temperature to obtain a curbstone.
[0104] Example 2
[0105] The composite ceramic glaze comprises the following raw materials in parts by weight: quartz: 35 parts; kaolin: 25 parts; feldspar: 30 parts; talc: 10 parts; boric acid: 5 parts; limestone: 15 parts; nano silicon dioxide: 3 parts; nano aluminum oxide: 4 parts; silver-loaded zeolite: 3 parts; nano titanium dioxide: 4 parts; zinc oxide: 3 parts; silicon powder: 2 parts; magnesium oxide: 2 parts; zirconium oxide: 3 parts; cerium oxide: 1.5 parts; lanthanum oxide: 2 parts; lithium fluoride: 3 parts; luminescent phosphor: 3 parts; long afterglow phosphor: 2 parts; also includes sodium hexametaphosphate, bentonite and water.
[0106] The silicon dioxide content in quartz is 98%; the kaolinite content in kaolin is 85%; the potassium feldspar content in feldspar is 55%, the sodium feldspar content is 30%, and the calcium feldspar content is 15%; the hydrated magnesium silicate content in talc is 94%; the montmorillonite content in bentonite is 86%; the silver content in silver-loaded zeolite is 3.2%.
[0107] The preparation method of the luminescent phosphor comprises the following steps:
[0108] (1) Weigh Y (NO3)3•6H2O, Eu (NO3)3•6H2O and Mg (NO3)2•6H2O, dissolve them in deionized water, and stir for 20 min to form solution A;
[0109] (2) Dissolve citric acid in deionized water, add NH4VO3, and stir for 30 min to form solution B;
[0110] (3) Solution A was added dropwise to solution B while stirring continuously for 1.5 h to form a sol; the sol was then placed in an oven and dried at 65 °C for 2 h to form a gel; the temperature was then raised to 135 °C and dried for 5 h to remove residual moisture and organic matter; the dried gel was ground into powder;
[0111] (4) placing the powder obtained in step (3) in a muffle furnace protected by nitrogen, calcining at 735° C. for 5 h, and then starting to cool down, first at a rate of 3° C. / min to 500° C., and then at a rate of 15° C. / min to room temperature, to obtain a luminescent phosphor base material;
[0112] (5) taking the luminescent phosphor base material obtained in step (4), dispersing it in anhydrous ethanol, and ultrasonically treating it for 30 minutes to form a suspension C;
[0113] (6) Take ethyl orthosilicate, add it to anhydrous ethanol, stir for 20 minutes, and form solution D;
[0114] (7) Add the suspension C dropwise into the solution D while stirring, add ammonia water, adjust the pH value to 9, and stir for 2.5 hours to promote the hydrolysis and polycondensation reaction of tetraethyl orthosilicate. After the reaction is completed, centrifuge the obtained product, collect the precipitate, wash the precipitate with anhydrous ethanol for 3 times, and then dry the precipitate at 75°C for 3 hours to obtain a luminescent phosphor;
[0115] The molar ratio of Y (NO3)3•6H2O, Eu (NO3)3•6H2O, Mg (NO3)2•6H2O and NH4VO3 is 0.9:0.05:0.02:1; the amount of citric acid used is 1.2 times the amount of the total amount of metal ions; the mass ratio of the luminescent phosphor base material to tetraethyl orthosilicate is 1:0.8; the total amount of anhydrous ethanol used is 7 times the volume of tetraethyl orthosilicate; in step (1), the amount of deionized water used is 3 times the sum of the masses of Y(NO3)3•6H2O, Eu (NO3)3•6H2O and Mg (NO3)2•6H2O; in step (2), the amount of deionized water used is 2 times the mass of citric acid; in step (3), the dripping speed is 1 ml / min.
[0116] The method for preparing a long afterglow phosphor comprises the following steps:
[0117] ① Dissolve Ca (NO3)2•4H2O, Dy (NO3)3•6H2O and Zr (NO4)4•5H2O in deionized water and stir for 15 minutes to form solution E;
[0118] ② Dissolve Na2MoO4•2H2O in deionized water to form solution F;
[0119] ③ Add solution F drop by drop into solution E while stirring, adjust the pH value to 8.5 with NaOH solution, then transfer it to a hydrothermal reactor, place it in an oven, and react at 170°C for 18 hours. After the reaction is completed, centrifuge the product, wash the precipitate with deionized water and anhydrous ethanol three times, and dry it at 65°C for 5 hours to obtain a long afterglow phosphor base material;
[0120] ④ Disperse the long afterglow phosphor base material into deionized water and perform ultrasonic treatment for 0.5 h to form a suspension G;
[0121] ⑤ Dissolve Al (NO3)3•9H2O in deionized water to form solution H;
[0122] ⑥ Add solution H drop by drop into suspension G, start stirring at the same time, add ammonia water, adjust the pH value to 9.5, promote the hydrolysis and polycondensation reaction of Al (NO3)3•9H2O, and after the reaction is completed, centrifuge the obtained product, wash the precipitate with deionized water and anhydrous ethanol three times, and dry it at 75℃ for 2.5h to obtain long afterglow phosphor;
[0123] The molar ratio of Ca (NO3)2•4H2O, Na2MoO4•2H2O, Dy (NO3)3•6H2O and Zr (NO4)4•5H2O is 1:0.9:0.05:0.02; the mass ratio of long afterglow phosphor base material to Al (NO3)3•9H2O is 1:0.6; in step ①, the amount of deionized water is 3.5 times the sum of the masses of Ca (NO3)2•4H2O, Dy (NO3)3•6H2O and Zr (NO4)4•5H2O; in step ②, the amount of deionized water is 4 times the mass of Na2MoO4•2H2O; in step ③, the dripping speed is 4ml / min; in step ④, the amount of deionized water is 5 times the mass of long afterglow phosphor base material; in step ⑤, the amount of deionized water is Al 5 times the mass of (NO3)3•9H2O; in step ⑥, when solution H is added dropwise to suspension G, the dropping speed is 3 ml / min, and the dropping speed of ammonia water is 2 ml / min.
[0124] The particle size of talc is 8 microns; the nano silicon dioxide is compounded by 12 nanometers and 62 nanometers silicon dioxide in a mass ratio of 2:1; the particle size of nano alumina is 20 nanometers; the particle size of nano titanium dioxide is 25 nanometers; the particle size of silver-loaded zeolite is 3 microns; the particle size of luminescent phosphor is 25 microns; and the particle size of long afterglow phosphor is 25 microns.
[0125] The preparation method of the composite ceramic glaze comprises the following steps:
[0126] a. Screening of quartz, kaolin, feldspar and limestone, with particle size controlled at 80 microns;
[0127] b. Place nano-silicon dioxide, nano-alumina and nano-titanium dioxide in different mixers, add sodium hexametaphosphate respectively, mix for 1.5 hours, combine the materials in the three mixers, and continue mixing for 3 hours to obtain a nano-mixture; the mass ratio of sodium hexametaphosphate to nano-silicon dioxide is 5:100, the mass ratio of sodium hexametaphosphate to nano-alumina is 2:100, and the mass ratio of sodium hexametaphosphate to nano-titanium dioxide is 1.5:100;
[0128] c. The quartz, kaolin, and feldspar are placed in a mixing device for mixing, the mixing time is 70min, and then talc, boric acid, limestone, and silica powder are added, and stirring and mixing is continued for 60min, and then the nano-mixture prepared in step b is added, and stirring and mixing is continued for 3h, and then zinc oxide and magnesium oxide are added, and after stirring for 50min, silver-loaded zeolite, zirconium oxide, cerium oxide, and lanthanum oxide are added, and after stirring for 45min, lithium fluoride, luminescent phosphor and long afterglow phosphor are added, and the stirring speed is reduced, and stirring is continued for 3h to obtain a mixed powder;
[0129] d. The mixed powder obtained in step c is placed in a ball mill and milled for 18h, and the particle size after ball milling is not greater than 42 microns;
[0130] e. Stir the ball-milled mixed powder with water and bentonite for 4.5 hours to obtain a composite ceramic glaze.
[0131] The amount of water added is 35% of the total mass of the glaze; the amount of bentonite added is 3.8% of the total mass of the glaze.
[0132] The curbstone blank includes the following raw materials in parts by weight: clay: 42 parts; quartz: 21 parts; feldspar: 15 parts; talc: 3 parts; limestone: 3 parts; boric acid: 1 part; titanium dioxide: 1 part; magnesium oxide: 2 parts; nano zirconium oxide: 2 parts; nano aluminum oxide: 2 parts; carboxymethyl cellulose: 1 part; silica sol: 4 parts.
[0133] The method for preparing the kerbstone comprises the following steps:
[0134] (I) crushing and sieving clay, quartz, feldspar, talc, limestone, boric acid, titanium dioxide and magnesium oxide to obtain a mixture with a particle size of 25 microns as a mixed raw material;
[0135] (II) Take nano zirconium oxide and nano alumina, place them in different containers, add ethanol for ultrasonic dispersion, ultrasonicate for 1.5 hours, and then dry at 65°C for 80 minutes to obtain nano powder zirconium oxide and nano powder alumina; dissolve carboxymethyl cellulose in water while stirring to form a carboxymethyl cellulose solution, the dissolution temperature is 55°C; take silica sol and stir for 1.5 hours;
[0136] (III) placing the mixed raw materials in step (I), the nano-powder zirconium oxide and nano-powder aluminum oxide in step (II), the carboxymethyl cellulose solution and the stirred silica sol in a ball mill in sequence, and performing ball milling mixing for 26 hours. After the mixing is completed, extrusion molding is performed to obtain a curbstone blank;
[0137] (IV) drying the curbstone body by microwave drying for 6 hours at a drying temperature of 45°C. After drying, dipping the body in a composite ceramic glaze for 12 seconds. After dipping, drying the body at a temperature of 28°C and a relative humidity of 50% for 18 hours.
[0138] (V) The green body after glaze dipping and drying is placed in a microwave sintering furnace, and a mixed gas of hydrogen and nitrogen (the volume ratio of hydrogen and nitrogen is 12:92) is introduced for protection. The temperature is increased to 465°C at a rate of 8°C / min, and kept at this temperature for 1 hour. Then, the temperature is increased to 990°C at a rate of 10°C / min, and kept at this temperature for 3 hours. Then, the temperature is decreased to 300°C at a rate of 7°C / min, and then naturally cooled to room temperature to obtain a curbstone.
[0139] Example 3
[0140] The composite ceramic glaze comprises the following raw materials in parts by weight: quartz: 20 parts; kaolin: 15 parts; feldspar: 20 parts; talc: 4 parts; boric acid: 2 parts; limestone: 8 parts; nano silicon dioxide: 1 part; nano aluminum oxide: 1 part; silver-loaded zeolite: 1 part; nano titanium dioxide: 1 part; zinc oxide: 1 part; silicon powder: 1 part; magnesium oxide: 1 part; zirconium oxide: 1 part; cerium oxide: 0.5 part; lanthanum oxide: 0.5 part; lithium fluoride: 0.5 part; luminescent phosphor: 0.5 part; long afterglow phosphor: 0.5 part; also comprises sodium hexametaphosphate, bentonite and water.
[0141] The silicon dioxide content in quartz is 96%; the kaolinite content in kaolin is 80%; the potassium feldspar content in feldspar is 46%, the sodium feldspar content is 36%, and the calcium feldspar content is 18%; the hydrated magnesium silicate content in talc is 94%; the montmorillonite content in bentonite is 89%; the silver content in silver-loaded zeolite is 1.3%.
[0142] The preparation method of the luminescent phosphor comprises the following steps:
[0143] (1) Weigh Y (NO3)3•6H2O, Eu (NO3)3•6H2O and Mg (NO3)2•6H2O, dissolve them in deionized water, and stir for 30 min to form solution A;
[0144] (2) Dissolve citric acid in deionized water, add NH4VO3, and stir for 40 min to form solution B;
[0145] (3) Add solution A dropwise to solution B while stirring continuously for 2 h to form a sol; then place in an oven and dry at 75 °C for 3 h to form a gel; then heat to 155 °C and dry for 8 h to remove residual moisture and organic matter; grind the dried gel into powder;
[0146] (4) placing the powder obtained in step (3) in a muffle furnace protected by nitrogen, calcining at 750° C. for 8 h, and then starting to cool down, first at a rate of 5° C. / min to 500° C., and then at a rate of 18° C. / min to room temperature, to obtain a luminescent phosphor base material;
[0147] (5) taking the luminescent phosphor base material obtained in step (4), dispersing it in anhydrous ethanol, and ultrasonically treating it for 45 minutes to form a suspension C;
[0148] (6) Take ethyl orthosilicate, add it to anhydrous ethanol, stir for 25 minutes, and form solution D;
[0149] (7) Add the suspension C dropwise into the solution D while stirring, add ammonia water, adjust the pH value to 10, and stir for 4 h to promote the hydrolysis and polycondensation reaction of tetraethyl orthosilicate. After the reaction is completed, centrifuge the obtained product, collect the precipitate, wash the precipitate with anhydrous ethanol 5 times, and then dry the precipitate at 80 ° C for 5 h to obtain a luminescent phosphor;
[0150] The molar ratio of Y (NO3)3•6H2O, Eu (NO3)3•6H2O, Mg (NO3)2•6H2O and NH4VO3 is 0.95:0.05:0.03:1; the amount of citric acid used is 2.2 times the amount of the total amount of metal ions; the mass ratio of the luminescent phosphor base material to tetraethyl orthosilicate is 1:1.2; the total amount of anhydrous ethanol used is 9 times the volume of tetraethyl orthosilicate; in step (1), the amount of deionized water used is 4 times the sum of the masses of Y (NO3)3•6H2O, Eu (NO3)3•6H2O and Mg (NO3)2•6H2O; in step (2), the amount of deionized water used is 3 times the mass of citric acid; in step (3), the dripping speed is 3 ml / min.
[0151] The method for preparing a long afterglow phosphor comprises the following steps:
[0152] ① Dissolve Ca (NO3)2•4H2O, Dy (NO3)3•6H2O and Zr (NO4)4•5H2O in deionized water and stir for 25 min to form solution E;
[0153] ② Dissolve Na2MoO4•2H2O in deionized water to form solution F;
[0154] ③ Add solution F drop by drop into solution E while stirring, adjust the pH value to 9 with NaOH solution, then transfer it to a hydrothermal reactor, place it in an oven, and react at 178°C for 24 hours. After the reaction, centrifuge the product, wash the precipitate with deionized water and anhydrous ethanol for 5 times, and dry it at 75°C for 8 hours to obtain a long afterglow phosphor base material;
[0155] ④ Disperse the long afterglow phosphor base material into deionized water and perform ultrasonic treatment for 1 hour to form a suspension G;
[0156] ⑤ Dissolve Al (NO3)3•9H2O in deionized water to form solution H;
[0157] ⑥ Add solution H drop by drop into suspension G, start stirring at the same time, add ammonia water, adjust the pH value to 10, promote the hydrolysis and polycondensation reaction of Al (NO3)3•9H2O, and after the reaction is completed, centrifuge the obtained product, wash the precipitate with deionized water and anhydrous ethanol 5 times, and dry it at 80℃ for 3 hours to obtain long afterglow phosphor;
[0158] The molar ratio of Ca (NO3)2•4H2O, Na2MoO4•2H2O, Dy (NO3)3•6H2O and Zr (NO4)4•5H2O is 1:0.94:0.05:0.03; the mass ratio of long afterglow phosphor base material to Al (NO3)3•9H2O is 1:1; in step ①, the amount of deionized water is twice the sum of the masses of Ca (NO3)2•4H2O, Dy (NO3)3•6H2O and Zr (NO4)4•5H2O; in step ②, the amount of deionized water is twice the mass of Na2MoO4•2H2O; in step ③, the dripping speed is 1.5ml / min; in step ④, the amount of deionized water is 3 times the mass of long afterglow phosphor base material; in step ⑤, the amount of deionized water is Al 3 times the mass of (NO3)3•9H2O; in step ⑥, when solution H is added dropwise to suspension G, the dropping speed is 1.5 ml / min, and the dropping speed of ammonia water is 1 ml / min.
[0159] The particle size of talc is 20 microns; nano silicon dioxide is compounded by 28 nanometers and 74 nanometers silicon dioxide in a mass ratio of 2:1; the particle size of nano alumina is 35 nanometers; the particle size of nano titanium dioxide is 35 nanometers; the particle size of silver-loaded zeolite is 7 microns; the particle size of luminescent phosphor is 32 microns; and the particle size of long afterglow phosphor is 35 microns.
[0160] The preparation method of the composite ceramic glaze comprises the following steps:
[0161] a. Screening of quartz, kaolin, feldspar and limestone, with particle size controlled at 50 microns;
[0162] b. Place nano-silicon dioxide, nano-alumina and nano-titanium dioxide in different mixers, add sodium hexametaphosphate respectively, mix for 1 hour, combine the materials in the three mixers, and continue mixing for 2 hours to obtain a nano-mixture; the mass ratio of sodium hexametaphosphate to nano-silicon dioxide is 4:100, the mass ratio of sodium hexametaphosphate to nano-alumina is 1:100, and the mass ratio of sodium hexametaphosphate to nano-titanium dioxide is 1:100;
[0163] c. The quartz, kaolin, and feldspar are placed in a mixing device for mixing, the mixing time is 30min, and then talc, boric acid, limestone, and silica powder are added, and stirring and mixing is continued for 45min, and then the nano-mixture prepared in step b is added, and stirring and mixing is continued for 2h, and then zinc oxide and magnesium oxide are added, and after stirring for 35min, silver-loaded zeolite, zirconium oxide, cerium oxide, and lanthanum oxide are added, and after stirring for 30min, lithium fluoride, luminescent phosphor and long afterglow phosphor are added, and the stirring speed is reduced, and stirring is continued for 2h to obtain a mixed powder;
[0164] d. The mixed powder obtained in step c is placed in a ball mill and milled for 12h, and the particle size after ball milling is not greater than 42 microns;
[0165] e. Stir the ball-milled mixed powder with water and bentonite for 3 hours to obtain a composite ceramic glaze.
[0166] The amount of water added is 32% of the total mass of the glaze; the amount of bentonite added is 3.2% of the total mass of the glaze.
[0167] The curbstone blank comprises the following raw materials in parts by weight: clay: 35 parts; quartz: 18 parts; feldspar: 12 parts; talc: 2 parts; limestone: 1 part; boric acid: 0.5 parts; titanium dioxide: 0.5 parts; magnesium oxide: 1 part; nano zirconium oxide: 1 part; nano aluminum oxide: 1 part; carboxymethyl cellulose: 0.5 parts; and silica sol: 2 parts.
[0168] The method for preparing the kerbstone comprises the following steps:
[0169] (I) crushing and sieving clay, quartz, feldspar, talc, limestone, boric acid, titanium dioxide and magnesium oxide to obtain a mixture with a particle size of 15 microns as a mixed raw material;
[0170] (II) Take nano zirconium oxide and nano alumina, place them in different containers, add ethanol for ultrasonic dispersion, ultrasonic for 1 hour, and then dry at 50°C for 60 minutes to obtain nano powder zirconium oxide and nano powder alumina; dissolve carboxymethyl cellulose in water while stirring to form a carboxymethyl cellulose solution, the dissolution temperature is 45°C; take silica sol and stir for 1 hour;
[0171] (III) placing the mixed raw materials in step (I), the nano-powdered zirconium oxide and nano-powdered aluminum oxide in step (II), the carboxymethyl cellulose solution and the stirred silica sol in a ball mill in sequence, and performing ball milling mixing for 18 hours. After the mixing is completed, extrusion molding is performed to obtain a curbstone blank;
[0172] (IV) drying the curbstone body by microwave drying for 3 hours at a drying temperature of 35°C. After drying, dipping the body in a composite ceramic glaze for 8 seconds. After dipping, drying the body at a temperature of 25°C and a relative humidity of 50% for 12 hours.
[0173] (V) The green body after glaze dipping and drying is placed in a microwave sintering furnace, and a mixed gas of hydrogen and nitrogen (the volume ratio of hydrogen and nitrogen is 8:80) is introduced for protection. The temperature is increased to 465°C at a rate of 8°C / min, and kept at this temperature for 1 hour. Then, the temperature is increased to 975°C at a rate of 10°C / min, and kept at this temperature for 3 hours. Then, the temperature is decreased to 300°C at a rate of 7°C / min, and then naturally cooled to room temperature to obtain a curbstone.
[0174] Example 4
[0175] The composite ceramic glaze comprises the following raw materials in parts by weight: quartz: 30 parts; kaolin: 20 parts; feldspar: 25 parts; talc: 8 parts; boric acid: 3 parts; limestone: 12 parts; nano silicon dioxide: 2 parts; nano aluminum oxide: 3 parts; silver-loaded zeolite: 2 parts; nano titanium dioxide: 3 parts; zinc oxide: 2 parts; silicon powder: 2 parts; magnesium oxide: 2 parts; zirconium oxide: 2 parts; cerium oxide: 1 part; lanthanum oxide: 1 part; lithium fluoride: 2 parts; luminescent phosphor: 2 parts; long afterglow phosphor: 1 part; also comprises sodium hexametaphosphate, bentonite and water.
[0176] The silicon dioxide content in quartz is 97%; the kaolinite content in kaolin is 83%; the potassium feldspar content in feldspar is 50%, the sodium feldspar content is 36%, and the calcium feldspar content is 14%; the hydrated magnesium silicate content in talc is 93%; the montmorillonite content in bentonite is 88%; the silver content in silver-loaded zeolite is 2%.
[0177] The preparation method of the luminescent phosphor comprises the following steps:
[0178] (1) Weigh Y (NO3)3•6H2O, Eu (NO3)3•6H2O and Mg (NO3)2•6H2O, dissolve them in deionized water, and stir for 20 min to form solution A;
[0179] (2) Dissolve citric acid in deionized water, add NH4VO3, and stir for 30 min to form solution B;
[0180] (3) Solution A was added dropwise to solution B while stirring continuously for 1.5 h to form a sol; the sol was then placed in an oven and dried at 65 °C for 2 h to form a gel; the temperature was then raised to 135 °C and dried for 5 h to remove residual moisture and organic matter; the dried gel was ground into powder;
[0181] (4) placing the powder obtained in step (3) in a muffle furnace protected by nitrogen, calcining at 735° C. for 5 h, and then starting to cool down, first at a rate of 3° C. / min to 500° C., and then at a rate of 15° C. / min to room temperature, to obtain a luminescent phosphor base material;
[0182] (5) taking the luminescent phosphor base material obtained in step (4), dispersing it in anhydrous ethanol, and ultrasonically treating it for 45 minutes to form a suspension C;
[0183] (6) Take ethyl orthosilicate, add it to anhydrous ethanol, stir for 20 minutes, and form solution D;
[0184] (7) Add the suspension C dropwise into the solution D while stirring, add ammonia water, adjust the pH value to 9, and stir for 2.5 hours to promote the hydrolysis and polycondensation reaction of tetraethyl orthosilicate. After the reaction is completed, centrifuge the obtained product, collect the precipitate, wash the precipitate with anhydrous ethanol for 3 times, and then dry the precipitate at 75°C for 3 hours to obtain a luminescent phosphor;
[0185] The molar ratio of Y (NO3)3•6H2O, Eu (NO3)3•6H2O, Mg (NO3)2•6H2O and NH4VO3 is 0.9:0.05:0.02:1; the amount of citric acid used is 1.2 times the amount of the total amount of metal ions; the mass ratio of the luminescent phosphor base material to tetraethyl orthosilicate is 1:0.8; the total amount of anhydrous ethanol used is 7 times the volume of tetraethyl orthosilicate; in step (1), the amount of deionized water used is 2.5 times the sum of the masses of Y(NO3)3•6H2O, Eu (NO3)3•6H2O and Mg (NO3)2•6H2O; in step (2), the amount of deionized water used is 3 times the mass of citric acid; in step (3), the dripping speed is 1-3 ml / min.
[0186] The method for preparing a long afterglow phosphor comprises the following steps:
[0187] ① Dissolve Ca (NO3)2•4H2O, Dy (NO3)3•6H2O and Zr (NO4)4•5H2O in deionized water and stir for 15 minutes to form solution E;
[0188] ② Dissolve Na2MoO4•2H2O in deionized water to form solution F;
[0189] ③ Add solution F drop by drop into solution E while stirring, adjust the pH value to 8.5 with NaOH solution, then transfer it to a hydrothermal reactor, place it in an oven, and react at 170°C for 18 hours. After the reaction is completed, centrifuge the product, wash the precipitate with deionized water and anhydrous ethanol three times, and dry it at 65°C for 5 hours to obtain a long afterglow phosphor base material;
[0190] ④ Disperse the long afterglow phosphor base material into deionized water and perform ultrasonic treatment for 0.5 h to form a suspension G;
[0191] ⑤ Dissolve Al (NO3)3•9H2O in deionized water to form solution H;
[0192] ⑥ Add solution H drop by drop into suspension G, start stirring at the same time, add ammonia water, adjust the pH value to 9.5, promote the hydrolysis and polycondensation reaction of Al (NO3)3•9H2O, and after the reaction is completed, centrifuge the obtained product, wash the precipitate with deionized water and anhydrous ethanol three times, and dry it at 75℃ for 2.5h to obtain long afterglow phosphor;
[0193] The molar ratio of Ca (NO3)2•4H2O, Na2MoO4•2H2O, Dy (NO3)3•6H2O and Zr (NO4)4•5H2O is 1:0.9:0.05:0.02; the mass ratio of long afterglow phosphor base material to Al (NO3)3•9H2O is 1:0.6; in step ①, the amount of deionized water is 3.5 times the sum of the masses of Ca (NO3)2•4H2O, Dy (NO3)3•6H2O and Zr (NO4)4•5H2O; in step ②, the amount of deionized water is 4 times the mass of Na2MoO4•2H2O; in step ③, the dripping speed is 4ml / min; in step ④, the amount of deionized water is 5 times the mass of long afterglow phosphor base material; in step ⑤, the amount of deionized water is Al 5 times the mass of (NO3)3•9H2O; in step ⑥, when solution H is added dropwise to suspension G, the dropping speed is 3 ml / min, and the dropping speed of ammonia water is 2 ml / min.
[0194] The particle size of talc is 8 microns; the nano silicon dioxide is compounded by 12 nanometers and 62 nanometers silicon dioxide in a mass ratio of 2:1; the particle size of nano alumina is 20 nanometers; the particle size of nano titanium dioxide is 25 nanometers; the particle size of silver-loaded zeolite is 3 microns; the particle size of luminescent phosphor is 25 microns; and the particle size of long afterglow phosphor is 25 microns.
[0195] The preparation method of the composite ceramic glaze comprises the following steps:
[0196] a. Screening of quartz, kaolin, feldspar and limestone, with particle size controlled at 50 microns;
[0197] b. Place nano-silicon dioxide, nano-alumina and nano-titanium dioxide in different mixers, add sodium hexametaphosphate respectively, mix for 1 hour, combine the materials in the three mixers, and continue mixing for 2 hours to obtain a nano-mixture; the mass ratio of sodium hexametaphosphate to nano-silicon dioxide is 4:100, the mass ratio of sodium hexametaphosphate to nano-alumina is 1:100, and the mass ratio of sodium hexametaphosphate to nano-titanium dioxide is 1:100;
[0198] c. The quartz, kaolin, and feldspar are placed in a mixing device for mixing, the mixing time is 30min, and then talc, boric acid, limestone, and silica powder are added, and stirring and mixing is continued for 45min, and then the nano-mixture prepared in step b is added, and stirring and mixing is continued for 2h, and then zinc oxide and magnesium oxide are added, and after stirring for 35min, silver-loaded zeolite, zirconium oxide, cerium oxide, and lanthanum oxide are added, and after stirring for 30min, lithium fluoride, luminescent phosphor and long afterglow phosphor are added, and the stirring speed is reduced, and stirring is continued for 2h to obtain a mixed powder;
[0199] d. The mixed powder obtained in step c is placed in a ball mill and milled for 12h, and the particle size after ball milling is not greater than 42 microns;
[0200] e. Stir the ball-milled mixed powder with water and bentonite for 3 hours to obtain a composite ceramic glaze.
[0201] The amount of water added is 32% of the total mass of the glaze; the amount of bentonite added is 3.2% of the total mass of the glaze.
[0202] The curbstone blank comprises the following raw materials in parts by weight: clay: 35 parts; quartz: 18 parts; feldspar: 12 parts; talc: 2 parts; limestone: 1 part; boric acid: 0.5 parts; titanium dioxide: 0.5 parts; magnesium oxide: 1 part; nano zirconium oxide: 1 part; nano aluminum oxide: 1 part; carboxymethyl cellulose: 0.5 parts; and silica sol: 2 parts.
[0203] The method for preparing the kerbstone comprises the following steps:
[0204] (I) crushing and sieving clay, quartz, feldspar, talc, limestone, boric acid, titanium dioxide and magnesium oxide to obtain a mixture with a particle size of 15 microns as a mixed raw material;
[0205] (II) Take nano zirconium oxide and nano alumina, place them in different containers, add ethanol for ultrasonic dispersion, ultrasonic for 1 hour, and then dry at 50°C for 60 minutes to obtain nano powder zirconium oxide and nano powder alumina; dissolve carboxymethyl cellulose in water while stirring to form a carboxymethyl cellulose solution, the dissolution temperature is 45°C; take silica sol and stir for 1 hour;
[0206] (III) placing the mixed raw materials in step (I), the nano-powdered zirconium oxide and nano-powdered aluminum oxide in step (II), the carboxymethyl cellulose solution and the stirred silica sol in a ball mill in sequence, and performing ball milling mixing for 18 hours. After the mixing is completed, extrusion molding is performed to obtain a curbstone blank;
[0207] (IV) drying the curbstone body by microwave drying for 3 hours at a drying temperature of 45°C. After drying, dipping the body in a composite ceramic glaze for 8 seconds. After dipping, drying the body at a temperature of 25°C and a relative humidity of 50% for 12 hours.
[0208] (V) The green body after glaze dipping and drying is placed in a microwave sintering furnace, and a mixed gas of hydrogen and nitrogen (the volume ratio of hydrogen and nitrogen is 8:80) is introduced for protection. The temperature is increased to 465°C at a rate of 8°C / min, and kept at this temperature for 1 hour. Then, the temperature is increased to 975°C at a rate of 10°C / min, and kept at this temperature for 3 hours. Then, the temperature is decreased to 300°C at a rate of 7°C / min, and then naturally cooled to room temperature to obtain a curbstone.
[0209] Example 5
[0210] The composite ceramic glaze comprises the following raw materials in parts by weight: quartz: 20 parts; kaolin: 15 parts; feldspar: 20 parts; talc: 4 parts; boric acid: 2 parts; limestone: 8 parts; nano silicon dioxide: 1 part; nano aluminum oxide: 1 part; silver-loaded zeolite: 1 part; nano titanium dioxide: 1 part; zinc oxide: 1 part; silicon powder: 1 part; magnesium oxide: 1 part; zirconium oxide: 1 part; cerium oxide: 0.5 part; lanthanum oxide: 0.5 part; lithium fluoride: 0.5 part; luminescent phosphor: 0.5 part; long afterglow phosphor: 0.5 part; also comprises sodium hexametaphosphate, bentonite and water.
[0211] The silicon dioxide content in quartz is 96%; the kaolinite content in kaolin is 80%; the potassium feldspar content in feldspar is 46%, the sodium feldspar content is 36%, and the calcium feldspar content is 18%; the hydrated magnesium silicate content in talc is 94%; the montmorillonite content in bentonite is 87%; the silver content in silver-loaded zeolite is 1.3%.
[0212] The preparation method of the luminescent phosphor comprises the following steps:
[0213] (1) Weigh Y (NO3)3•6H2O, Eu (NO3)3•6H2O and Mg (NO3)2•6H2O, dissolve them in deionized water, and stir for 20 min to form solution A;
[0214] (2) Dissolve citric acid in deionized water, add NH4VO3, and stir for 30 min to form solution B;
[0215] (3) Solution A was added dropwise to solution B while stirring continuously for 1.5 h to form a sol; the sol was then placed in an oven and dried at 65 °C for 2 h to form a gel; the temperature was then raised to 135 °C and dried for 5 h to remove residual moisture and organic matter; the dried gel was ground into powder;
[0216] (4) placing the powder obtained in step (3) in a muffle furnace protected by nitrogen, calcining at 735° C. for 5 h, and then starting to cool down, first at a rate of 3° C. / min to 500° C., and then at a rate of 15° C. / min to room temperature, to obtain a luminescent phosphor base material;
[0217] (5) taking the luminescent phosphor base material obtained in step (4), dispersing it in anhydrous ethanol, and ultrasonically treating it for 40 minutes to form a suspension C;
[0218] (6) Take ethyl orthosilicate, add it to anhydrous ethanol, stir for 20 minutes, and form solution D;
[0219] (7) Add the suspension C dropwise into the solution D while stirring, add ammonia water, adjust the pH value to 9, and stir for 2.5 hours to promote the hydrolysis and polycondensation reaction of tetraethyl orthosilicate. After the reaction is completed, centrifuge the obtained product, collect the precipitate, wash the precipitate with anhydrous ethanol for 3 times, and then dry the precipitate at 75°C for 3 hours to obtain a luminescent phosphor;
[0220] The molar ratio of Y (NO3)3•6H2O, Eu (NO3)3•6H2O, Mg (NO3)2•6H2O and NH4VO3 is 0.9:0.05:0.02:1; the amount of citric acid used is 1.2 times the amount of the total amount of metal ions; the mass ratio of the luminescent phosphor base material to tetraethyl orthosilicate is 1:0.8; the total amount of anhydrous ethanol used is 7 times the volume of tetraethyl orthosilicate; in step (1), the amount of deionized water used is twice the sum of the masses of Y(NO3)3•6H2O, Eu (NO3)3•6H2O and Mg (NO3)2•6H2O; in step (2), the amount of deionized water used is twice the mass of citric acid; in step (3), the dripping speed is 2 ml / min.
[0221] The method for preparing a long afterglow phosphor comprises the following steps:
[0222] ① Dissolve Ca (NO3)2•4H2O, Dy (NO3)3•6H2O and Zr (NO4)4•5H2O in deionized water and stir for 15 minutes to form solution E;
[0223] ② Dissolve Na2MoO4•2H2O in deionized water to form solution F;
[0224] ③ Add solution F drop by drop into solution E while stirring, adjust the pH value to 8.5 with NaOH solution, then transfer it to a hydrothermal reactor, place it in an oven, and react at 170°C for 18 hours. After the reaction is completed, centrifuge the product, wash the precipitate with deionized water and anhydrous ethanol three times, and dry it at 65°C for 5 hours to obtain a long afterglow phosphor base material;
[0225] ④ Disperse the long afterglow phosphor base material into deionized water and perform ultrasonic treatment for 0.5 h to form a suspension G;
[0226] ⑤ Dissolve Al (NO3)3•9H2O in deionized water to form solution H;
[0227] ⑥ Add solution H drop by drop into suspension G, start stirring at the same time, add ammonia water, adjust the pH value to 9.5, promote the hydrolysis and polycondensation reaction of Al (NO3)3•9H2O, and after the reaction is completed, centrifuge the obtained product, wash the precipitate with deionized water and anhydrous ethanol three times, and dry it at 75℃ for 2.5h to obtain long afterglow phosphor;
[0228] The molar ratio of Ca (NO3)2•4H2O, Na2MoO4•2H2O, Dy (NO3)3•6H2O and Zr (NO4)4•5H2O is 1:0.9:0.05:0.02; the mass ratio of long afterglow phosphor base material to Al (NO3)3•9H2O is 1:0.6; in step ①, the amount of deionized water is twice the sum of the masses of Ca (NO3)2•4H2O, Dy (NO3)3•6H2O and Zr (NO4)4•5H2O; in step ②, the amount of deionized water is twice the mass of Na2MoO4•2H2O; in step ③, the dripping speed is 4ml / min; in step ④, the amount of deionized water is 5 times the mass of the long afterglow phosphor base material; in step ⑤, the amount of deionized water is Al 5 times the mass of (NO3)3•9H2O; in step ⑥, when solution H is added dropwise to suspension G, the dropping speed is 3 ml / min, and the dropping speed of ammonia water is 1 ml / min.
[0229] The particle size of talc is 8 microns; the nano silicon dioxide is compounded by 12 nanometers and 62 nanometers silicon dioxide in a mass ratio of 2:1; the particle size of nano alumina is 20 nanometers; the particle size of nano titanium dioxide is 25 nanometers; the particle size of silver-loaded zeolite is 3 microns; the particle size of luminescent phosphor is 25 microns; and the particle size of long afterglow phosphor is 25 microns.
[0230] The preparation method of the composite ceramic glaze comprises the following steps:
[0231] a. Screening of quartz, kaolin, feldspar and limestone, with particle size controlled at 65 microns;
[0232] b. Place nano-silicon dioxide, nano-alumina and nano-titanium dioxide in different mixers, add sodium hexametaphosphate respectively, mix for 1.5 hours, combine the materials in the three mixers, and continue mixing for 3 hours to obtain a nano-mixture; the mass ratio of sodium hexametaphosphate to nano-silicon dioxide is 5:100, the mass ratio of sodium hexametaphosphate to nano-alumina is 2:100, and the mass ratio of sodium hexametaphosphate to nano-titanium dioxide is 1.2:100;
[0233] c. The quartz, kaolin, and feldspar were placed in a mixing device for mixing, the mixing time was 70min, and then talc, boric acid, limestone, and silica powder were added, and stirring and mixing were continued for 50min, and then the nano-mixture prepared in step b was added, and stirring and mixing were continued for 3h, and then zinc oxide and magnesium oxide were added, and after stirring for 40min, silver-loaded zeolite, zirconium oxide, cerium oxide, and lanthanum oxide were added, and after stirring for 40min, lithium fluoride, luminescent phosphor and long afterglow phosphor were added, and the stirring speed was reduced and stirred for 3h to obtain a mixed powder;
[0234] d. The mixed powder obtained in step c was placed in a ball mill and milled for 16h, and the particle size after ball milling was 37 microns;
[0235] e. Stir the ball-milled mixed powder with water and bentonite for 4 hours to obtain a composite ceramic glaze.
[0236] The amount of water added is 35% of the total mass of the glaze; the amount of bentonite added is 3.6% of the total mass of the glaze.
[0237] The curbstone blank includes the following raw materials in parts by weight: clay: 40 parts; quartz: 20 parts; feldspar: 13 parts; talc: 3 parts; limestone: 2 parts; boric acid: 1 part; titanium dioxide: 1 part; magnesium oxide: 2 parts; nano zirconium oxide: 2 parts; nano aluminum oxide: 2 parts; carboxymethyl cellulose: 1 part; and silica sol: 3 parts.
[0238] The method for preparing the kerbstone comprises the following steps:
[0239] (I) crushing and sieving clay, quartz, feldspar, talc, limestone, boric acid, titanium dioxide and magnesium oxide to obtain a mixture with a particle size of 20 microns as a mixed raw material;
[0240] (II) Take nano zirconium oxide and nano alumina, place them in different containers, add ethanol for ultrasonic dispersion, ultrasonic for 1.2 hours, and then dry at 50°C for 70 minutes to obtain nano powder zirconium oxide and nano powder alumina; dissolve carboxymethyl cellulose in water while stirring to form a carboxymethyl cellulose solution, the dissolution temperature is 50°C; take silica sol and stir for 1.2 hours;
[0241] (III) placing the mixed raw materials in step (I), the nano-powdered zirconium oxide and nano-powdered aluminum oxide in step (II), the carboxymethyl cellulose solution and the stirred silica sol in a ball mill in sequence, and performing ball milling mixing for 22 hours. After the mixing is completed, extrusion molding is performed to obtain a curbstone blank;
[0242] (IV) drying the curbstone body by microwave drying for 5 hours at a drying temperature of 40°C. After drying, dipping the body in a composite ceramic glaze for 10 seconds. After dipping, drying the body at a temperature of 28°C and a relative humidity of 50% for 16 hours.
[0243] (V) The green body after glaze dipping and drying is placed in a microwave sintering furnace, and a mixed gas of hydrogen and nitrogen (the volume ratio of hydrogen and nitrogen is 10:90) is introduced for protection. The temperature is increased to 465°C at a rate of 8°C / min, and kept at this temperature for 1 hour. Then, the temperature is increased to 985°C at a rate of 10°C / min, and kept at this temperature for 4 hours. Then, the temperature is decreased to 300°C at a rate of 7°C / min, and then naturally cooled to room temperature to obtain a curbstone.
[0244] Comparative Example 1
[0245] Compared with Example 1, the difference is that no luminescent fluorescent powder is added.
[0246] Comparative Example 2
[0247] Compared with Example 1, the difference is that no long afterglow phosphor is added.
[0248] Comparative Example 3
[0249] Compared with Example 1, the difference is that the preparation method of the luminescent phosphor comprises the following steps:
[0250] (1) Weigh Y (NO3)3•6H2O and Eu (NO3)3•6H2O, dissolve them in deionized water, and stir for 30 min to form solution A;
[0251] (2) Dissolve citric acid in deionized water, add NH4VO3, and stir for 40 min to form solution B;
[0252] (3) Add solution A dropwise to solution B while stirring continuously for 2 h to form a sol; then place in an oven and dry at 70 °C for 3 h to form a gel; then heat to 145 °C and dry for 6 h to remove residual moisture and organic matter; grind the dried gel into powder;
[0253] (4) placing the powder obtained in step (3) in a muffle furnace protected by nitrogen, calcining at 740° C. for 6 hours, and then starting to cool down, first at a rate of 4° C. / min to 500° C., and then at a rate of 16° C. / min to room temperature, to obtain a luminescent phosphor base material;
[0254] The molar ratio of Y (NO3)3•6H2O, Eu (NO3)3•6H2O, and NH4VO3 is 0.92:0.05:1; the amount of citric acid used is twice the amount of the total amount of metal ions; in step (1), the amount of deionized water used is 2.5 times the sum of the masses of Y (NO3)3•6H2O and Eu (NO3)3•6H2O; in step (2), the amount of deionized water used is 3 times the mass of citric acid; in step (3), the dripping speed is 3 ml / min.
[0255] When preparing the composite ceramic glaze, the luminescent phosphor base material is added as a raw material.
[0256] Comparative Example 4
[0257] Compared with Example 1, the difference is that the preparation method of the long afterglow phosphor comprises the following steps:
[0258] ① Dissolve Ca (NO3)2•4H2O and Dy (NO3)3•6H2O in deionized water and stir for 20 minutes to form solution E;
[0259] ② Dissolve Na2MoO4•2H2O in deionized water to form solution F;
[0260] ③ Add solution F drop by drop into solution E while stirring, adjust the pH value to 8.8 with NaOH solution, then transfer it to a hydrothermal reactor, place it in an oven, and react at 178°C for 20 hours. After the reaction, centrifuge the product, wash the precipitate with deionized water and anhydrous ethanol 5 times, and dry it at 70°C for 8 hours to obtain a long afterglow phosphor base material;
[0261] The molar ratio of Ca (NO3)2•4H2O, Na2MoO4•2H2O and Dy (NO3)3•6H2O is 1:0.92:0.05; in step ①, the amount of deionized water used is twice the sum of the masses of Ca (NO3)2•4H2O and Dy (NO3)3•6H2O; in step ②, the amount of deionized water used is twice the mass of Na2MoO4•2H2O; in step ③, the dropping speed is 4 ml / min.
[0262] When preparing the composite ceramic glaze, the long afterglow phosphor base material is added as a raw material.
[0263] Comparative Example 5
[0264] Compared with Example 1, the difference is:
[0265] The composite ceramic glaze comprises the following raw materials in parts by weight: quartz: 30 parts; kaolin: 20 parts; limestone: 12 parts; nano silicon dioxide: 2 parts; nano aluminum oxide: 3 parts; silver-loaded zeolite: 2 parts; nano titanium dioxide: 3 parts; zinc oxide: 2 parts; silicon powder: 2 parts; magnesium oxide: 2 parts; bentonite: 3 parts; zirconium oxide: 2 parts; luminescent phosphor: 2 parts; long afterglow phosphor: 1 part.
[0266] The silicon dioxide content in quartz is 97%; the kaolinite content in kaolin is 83%; the montmorillonite content in bentonite is 88%; and the silver content in silver-loaded zeolite is 2%.
[0267] The nano silicon dioxide is compounded by mixing 20 nanometers and 70 nanometers silicon dioxide in a mass ratio of 2:1; the particle size of the nano aluminum oxide is 30 nanometers; the particle size of the nano titanium dioxide is 30 nanometers; the particle size of the silver-loaded zeolite is 5 micrometers; the particle size of the luminescent phosphor is 30 micrometers; and the particle size of the long afterglow phosphor is 30 micrometers.
[0268] The preparation method of the composite ceramic glaze comprises the following steps:
[0269] a. Screen quartz, kaolin and limestone to control the particle size to 65 microns;
[0270] b. Place nano-silicon dioxide, nano-alumina and nano-titanium dioxide in different mixers, add sodium hexametaphosphate respectively, mix for 1.5 hours, combine the materials in the three mixers, and continue mixing for 3 hours to obtain a nano-mixture; the mass ratio of sodium hexametaphosphate to nano-silicon dioxide is 5:100, the mass ratio of sodium hexametaphosphate to nano-alumina is 2:100, and the mass ratio of sodium hexametaphosphate to nano-titanium dioxide is 1.2:100;
[0271] c. The quartz, kaolin, placed in a mixing device for mixing, the mixing time is 30min, then add limestone, silica powder, continue stirring and mixing for 50min, then add the nano-mixture prepared in step b, continue stirring and mixing for 3h, then add zinc oxide, magnesium oxide, after stirring for 40min, add silver-loaded zeolite, zirconium oxide, after stirring for 40min, add luminescent phosphor and long afterglow phosphor, reduce the stirring speed, stir for 3h to obtain a mixed powder;
[0272] d. The mixed powder obtained in step c was placed in a ball mill and milled for 16h, and the particle size after ball milling was 37 microns;
[0273] e. Stir the ball-milled mixed powder with water and bentonite for 4 hours to obtain a composite ceramic glaze.
[0274] Comparative Example 6
[0275] Compared with Example 1, the difference is:
[0276] The preparation method of the composite ceramic glaze comprises the following steps:
[0277] a. Screening of quartz, kaolin, feldspar and limestone, with particle size controlled at 65 microns;
[0278] b. Place nano-silicon dioxide, nano-alumina and nano-titanium dioxide in different mixers, mix for 1.5 hours, combine the materials in the three mixers into one place, and continue mixing for 3 hours to obtain a nano-mixture;
[0279] c. Quartz, kaolin, feldspar, talc, boric acid, limestone, silica powder, stirred and mixed for 50min, then added the nano-mixture obtained in step b, continued stirring and mixing for 3h, then added zinc oxide, magnesium oxide, stirred for 40min, added silver-loaded zeolite, zirconium oxide, cerium oxide, lithium fluoride, lanthanum oxide, stirred for 40min, added luminescent phosphor and long afterglow phosphor, reduced the stirring speed, stirred for 3h to obtain a mixed powder;
[0280] d. The mixed powder obtained in step c was placed in a ball mill and milled for 16h, and the particle size after ball milling was 37 microns;
[0281] e. Stir the ball-milled mixed powder with water and bentonite for 4 hours to obtain a composite ceramic glaze.
[0282] Comparative Example 7
[0283] Compared with Example 1, the difference is:
[0284] The kerbstone blank comprises the following raw materials in parts by weight: clay: 40 parts; quartz: 20 parts; feldspar: 13 parts; talc: 3 parts; limestone: 2 parts; boric acid: 1 part; titanium dioxide: 1 part; magnesium oxide: 2 parts; and carboxymethyl cellulose: 1 part.
[0285] Correspondingly, the method for preparing the kerbstone is prepared according to the above raw materials.
[0286] Comparative Example 8
[0287] Compared with Example 1, the difference is:
[0288] The method for preparing the kerbstone comprises the following steps:
[0289] (I) crushing and sieving clay, quartz, feldspar, talc, limestone, boric acid, titanium dioxide and magnesium oxide to obtain a mixture with a particle size of 20 microns as a mixed raw material;
[0290] (II) Take nano zirconium oxide and nano alumina, place them in different containers, add ethanol for ultrasonic dispersion, ultrasonicate for 1.2 hours, and then dry at 65°C for 70 minutes to obtain nano powder zirconium oxide and nano powder alumina; dissolve carboxymethyl cellulose in water while stirring to form a carboxymethyl cellulose solution, the dissolution temperature is 50°C; take silica sol and stir for 1.2 hours;
[0291] (III) placing the mixed raw materials in step (I), the nano-powdered zirconium oxide and nano-powdered aluminum oxide in step (II), the carboxymethyl cellulose solution and the stirred silica sol in a ball mill in sequence, and performing ball milling mixing for 22 hours. After the mixing is completed, extrusion molding is performed to obtain a curbstone blank;
[0292] (IV) drying the curbstone body by microwave drying for 5 hours at a drying temperature of 52°C. After drying, dipping the body in a composite ceramic glaze for 10 seconds. After dipping, drying the body at a temperature of 28°C and a relative humidity of 50% for 16 hours.
[0293] (V) Place the glaze-impregnated and dried body in a muffle furnace, heat it to 465°C at a rate of 8°C / min, keep it at that temperature for 1 hour, then heat it to 985°C at a rate of 10°C / min, keep it at that temperature for 4 hours, then cool it to 300°C at a rate of 7°C / min, and then naturally cool it to room temperature to obtain a curbstone.
[0294] The test data of Examples 1-5 and Comparative Examples 1-8 are shown in Table 1.
[0295] Table 1 Test data of Examples 1-5 and Comparative Examples 1-8
[0296]
[0297] It can be seen from the above data that the effect of Example 1 is the most excellent, which is obtained by the combined effect of various raw material compounds and corresponding preparation methods. Compared with Example 1, in the case of lack of fluorescent powder in the raw materials of Comparative Examples 1 and Comparative Example 2 (Comparative Example 1 does not add luminescent fluorescent powder, and Comparative Example 2 does not add long afterglow fluorescent powder), the fluorescence intensity is significantly reduced. Comparative Example 3 does not perform corresponding treatment on the luminescent fluorescent powder, which leads to changes in the main structure during the subsequent high-temperature sintering process, resulting in a significant decrease in the fluorescence effect. Comparative Example 4 is the same as Comparative Example 3. Comparative Example 5 has incomplete sintering due to changes in the glaze formula, which in turn affects its performance. In Comparative Example 6, the nanomaterials were not treated in advance, resulting in partial agglomeration and a significant decrease in performance. In Comparative Example 7, the formula of the blank was changed, resulting in cracks on the surface of the product. In Comparative Example 8, it was mainly because microwave sintering was not used, resulting in insufficient sintering temperature. In order to use atmosphere protection, the phosphor was partially oxidized at high temperature, and its performance was significantly reduced. By attaching Figure 2 It can be seen that the excitation spectrum of the material prepared in Example 1 is mainly concentrated at 320 nanometers (Dy 3+ ions 4f - 5d transition), 380 nm (Dy 3+ 4f - 5d transition of ions and Eu 3+ The 4f electron of the ion jumps to a higher energy level: 7 F 0.1 → 5 L7), 430 nm (Eu 3+ ions) and 450 nm (Eu 3+ ions) and in the range of 300-700 nanometers emitted by car lights; Figure 3 It can be seen that the material prepared in Example 1 has a long afterglow time. When the afterglow is 3h, it can still maintain 0.12mcd / m 2 The above strength is suitable for guiding at night.
Claims
1. A composite ceramic glaze, characterized in that: The invention comprises the following raw materials in parts by weight: quartz: 20-35 parts; kaolin: 15-25 parts; feldspar: 20-30 parts; Talc: 4-10 parts; Boric acid: 2-5 parts; limestone: 8-15 parts; nano silicon dioxide: 1-3 parts; nano alumina: 1-4 parts; silver-loaded zeolite: 1-3 parts; nano titanium dioxide: 1-4 parts; Zinc oxide: 1-3 parts; Silicon powder: 1-2 parts; Magnesium oxide: 1-2 parts; Zirconia: 1-3 parts; Cerium oxide: 0.5-1.5 parts; Lanthanum oxide: 0.5-2 parts; Lithium fluoride: 0.5-3 parts; Luminescent phosphor: 0.5-3 parts; Long afterglow phosphor: 0.5-2 parts; The method for preparing the luminescent fluorescent powder comprises the following steps: (1) Weigh Y (NO3)3•6H2O, Eu (NO3)3•6H2O and Mg (NO3)2•6H2O, dissolve them in deionized water, and stir for 20-30 min to form solution A; (2) Dissolve citric acid in deionized water, add NH4VO3, and stir for 30-40 minutes to form solution B; (3) Add solution A dropwise to solution B while stirring continuously for 1.5-2 hours to form a sol; then place in an oven and dry at 65-75°C for 2-3 hours to form a gel; then heat to 135-155°C and dry for 5-8 hours to remove residual moisture and organic matter; grind the dried gel into powder; (4) placing the powder obtained in step (3) in a muffle furnace protected by nitrogen, calcining at 735-750°C for 5-8 hours, and then starting to cool down, first at a rate of 3-5°C / min to 500°C, and then at a rate of 15-18°C / min to room temperature, to obtain a luminescent phosphor base material; (5) taking the luminescent phosphor base obtained in step (4), dispersing it in anhydrous ethanol, and ultrasonically treating it for 30-45 minutes to form a suspension C; (6) Take ethyl orthosilicate, add it to anhydrous ethanol, stir for 20-25 minutes, and form solution D; (7) Add the suspension C dropwise into the solution D while stirring, add ammonia water, adjust the pH value to 9-10, and stir for 2.5-4 hours to promote the hydrolysis and polycondensation reaction of tetraethyl orthosilicate. After the reaction is completed, centrifuge the obtained product, collect the precipitate, wash the precipitate with anhydrous ethanol for 3-5 times, and then dry the precipitate at 75-80°C for 3-5 hours to obtain a luminescent phosphor; The molar ratio of Y (NO3)3•6H2O, Eu (NO3)3•6H2O, Mg (NO3)2•6H2O and NH4VO3 is (0.9-0.95):0.05:(0.02-0.03):1; the amount of citric acid used is 1.2-2.2 times the amount of the total amount of metal ions; the mass ratio of the luminescent phosphor base material to tetraethyl orthosilicate is 1:(0.8-1.2); the total amount of anhydrous ethanol used is 7-9 times the volume of tetraethyl orthosilicate; in the step (1), the amount of deionized water used is 2-4 times the sum of the masses of Y (NO3)3•6H2O, Eu (NO3)3•6H2O and Mg (NO3)2•6H2O; in the step (2), the amount of deionized water used is 2-3 times the mass of citric acid; in the step (3), the dripping speed is 1-3 ml / min; The method for preparing the long afterglow phosphor comprises the following steps: ① Dissolve Ca (NO3)2•4H2O, Dy (NO3)3•6H2O and Zr (NO3)4•5H2O in deionized water and stir for 15-25 minutes to form solution E; ② Dissolve Na2MoO4•2H2O in deionized water to form solution F; ③ Add solution F drop by drop into solution E while stirring, adjust the pH value to 8.5-9 with NaOH solution, then transfer it to a hydrothermal reactor, place it in an oven, and react at 170-178°C for 18-24h. After the reaction, centrifuge the product, wash the precipitate with deionized water and anhydrous ethanol 3-5 times, and dry it at 65-75°C for 5-8h to obtain a long afterglow phosphor base material; ④ Disperse the long afterglow phosphor base material into deionized water and perform ultrasonic treatment for 0.5-1h to form a suspension G; ⑤ Dissolve Al (NO3)3•9H2O in deionized water to form solution H; ⑥ Add solution H drop by drop into suspension G, start stirring at the same time, add ammonia water, adjust the pH value to 9.5-10, promote the hydrolysis and polycondensation reaction of Al (NO3)3•9H2O, after the reaction is completed, centrifuge the obtained product, wash the precipitate with deionized water and anhydrous ethanol 3-5 times, and dry it at 75-80℃ for 2.5-3h to obtain long afterglow phosphor; The molar ratio of Ca (NO3)2•4H2O, Na2MoO4•2H2O, Dy (NO3)3•6H2O and Zr (NO3)4•5H2O is 1: (0.9-0.94): 0.05: (0.02-0.03); the mass ratio of the long afterglow phosphor base material to Al (NO3)3•9H2O is 1: (0.6-1); in the step ①, the amount of deionized water is Ca (NO3)2•4H2O, Dy (NO3)3•6H2O and Zr(NO3)4•5H2O. In step ②, the amount of deionized water is 2-4 times the mass of Na2MoO4•2H2O. In step ③, the dripping speed is 1.5-4ml / min. In step ④, the amount of deionized water is 3-5 times the mass of the long afterglow phosphor base material. In step ⑤, the amount of deionized water is 3-5 times the mass of Al (NO3)3•9H2O. In step ⑥, when solution H is added dropwise into suspension G, the dripping speed is 1.5-3ml / min, and the dripping speed of ammonia water is 1-2 ml / min.
2. The composite ceramic glaze according to claim 1, characterized in that: It also includes sodium hexametaphosphate, bentonite and water. The amount of bentonite added is 3.2-3.8% of the total mass of the glaze, and the amount of water added is 32-35% of the total mass of the glaze.
3. The composite ceramic glaze according to claim 2, characterized in that: The silicon dioxide content in the quartz is 96-98%; the kaolinite content in the kaolin is 80-85%; the potassium feldspar content in the feldspar is 46-55%, the sodium feldspar content is 27-36%, and the calcium feldspar content is 12-18%; the hydrated magnesium silicate content in the talc is 92-94%; the montmorillonite content in the bentonite is 86-89%; and the silver content in the silver-loaded zeolite is 1.3-3.2%.
4. The composite ceramic glaze according to claim 1, characterized in that: The particle size of the talc is 8-20 microns; the nano silicon dioxide is 12-28 nanometers and 62-74 nanometers silicon dioxide are compounded in a mass ratio of 2:1; the particle size of the nano aluminum oxide is 20-35 nanometers; the particle size of the nano titanium dioxide is 25-35 nanometers; the particle size of the silver-loaded zeolite is 3-7 microns; the particle size of the luminescent phosphor is 25-32 microns; and the particle size of the long afterglow phosphor is 25-35 microns.
5. A method for preparing the composite ceramic glaze according to any one of claims 1 to 4, characterized in that: The following steps are involved: a. Screening of quartz, kaolin, feldspar and limestone, with particle size controlled at 50-80 microns; b. Place nano-silicon dioxide, nano-alumina and nano-titanium dioxide in different mixers, add sodium hexametaphosphate, mix for 1-1.5 hours, combine the materials in the three mixers, and continue mixing for 2-3 hours to obtain a nano-mixture; c. The quartz, kaolin, and feldspar are placed in a mixing device for mixing, the mixing time is 30-70min, and then talc, boric acid, limestone, and silica powder are added, and stirring and mixing is continued for 45-60min, and then the nano-mixture prepared in step b is added, and stirring and mixing is continued for 2-3h, and then zinc oxide and magnesium oxide are added, and after stirring for 35-50min, silver-loaded zeolite, zirconium oxide, cerium oxide, and lanthanum oxide are added, and after stirring for 30-45min, lithium fluoride, luminescent phosphor and long afterglow phosphor are added, and the stirring speed is reduced, and stirring is continued for 2-3h to obtain a mixed powder; d. The mixed powder obtained in step c is placed in a ball mill and milled for 12-18h, and the particle size after ball milling is not greater than 42 microns; e. Stir the ball-milled mixed powder with water and bentonite for 3-4.5 hours to obtain a composite ceramic glaze.
6. A method for applying the composite ceramic glaze according to any one of claims 1 to 4, characterized in that: Used for the preparation of kerbstones.
7. The application method of the composite ceramic glaze according to claim 6, characterized in that: The method for preparing the kerbstone comprises the following steps: (I) crushing and sieving clay, quartz, feldspar, talc, limestone, boric acid, titanium dioxide and magnesium oxide to obtain a mixture with a particle size of 15-25 microns as a mixed raw material; (II) taking nano zirconium oxide and nano alumina, placing them in different containers, adding ethanol for ultrasonic dispersion, ultrasonication for 1-1.5 hours, and then drying at 50-65°C for 60-80 minutes to obtain nano powder zirconium oxide and nano powder alumina; dissolving carboxymethyl cellulose in water while stirring to form a carboxymethyl cellulose solution, the dissolution temperature of which is 45-55°C; taking silica sol, stirring for 1-1.5 hours; (III) placing the mixed raw materials in step (I), the nano-powdered zirconium oxide and nano-powdered aluminum oxide in step (II), the carboxymethyl cellulose solution and the stirred silica sol in a ball mill in sequence, and performing ball milling mixing for a mixing time of 18-26 hours. After the mixing is completed, extrusion molding is performed to obtain a curbstone blank; (IV) drying the curbstone body by microwave, the drying time is 3-6 hours, the drying temperature is 35-45°C, after the drying is completed, dipping the body in a composite ceramic glaze, the dipping time is 8-12 seconds, after the dipping is completed, drying at a temperature of 25-28°C and a relative humidity of 50% for 12-18 hours; (V) Place the green body after glaze dipping and drying in a microwave sintering furnace, heat it to 465°C at a heating rate of 8°C / min, keep it at this temperature for 1 hour, then heat it to 975-990°C at a heating rate of 10°C / min, keep it at this temperature for 3-4 hours, then cool it to 300°C at a heating rate of 7°C / min, and then naturally cool it to room temperature to obtain a curbstone.
8. The application method of the composite ceramic glaze according to claim 7, characterized in that: The kerbstone blank comprises the following raw materials in parts by weight: clay: 35-42 parts; Quartz: 18-21 parts; Feldspar: 12-15 parts; Talc: 2-3 parts; Limestone: 1-3 parts; Boric acid: 0.5-1 part; Titanium dioxide: 0.5-1 part; Magnesium oxide: 1-2 parts; Nano zirconium oxide: 1-2 parts; Nano aluminum oxide: 1-2 parts; Carboxymethyl cellulose: 0.5-1 parts; Silica sol: 2-4 parts; When the microwave sintering furnace is working, a mixed gas of hydrogen and nitrogen is introduced for protection.